Studi Deskriptif Tingkat Kecemasan Pra Operasi di Masa Pandemi Covid-19 - Saputro, Dwi Nugroho Heri; Putriningtyas, Dewi; Susanti, Diana; Ita, Hana Hariska; Oktavia, Sherly; Harianto, Yunus (FORIKES, 2022)
Covid-19 cases as of July 26, 2021 in Yogyakarta were 107445 cases. The number of recovered patients was 71,189, and the number of cases who died was 3,003. This study aims to describe the level of preoperative anxiety during the Covid-19 pandemic in 2021. This study was a quantitative study with a descriptive approach. The population in this study was the people who live in the city of Yogyakarta. The sample size was 96 respondents who were selected by purposive sampling technique. Data were collected through filling out a questionnaire about preoperative anxiety levels during the Covid-19 pandemic. Data were analyzed descriptively. The results showed that most of the people of Yogyakarta City experienced moderate levels of anxiety when facing surgery during the Covid-19 pandemic.Keywords: anxiety; preoperative; Covid-19 pandemic ABSTRAK Kasus Covid-19 per tanggal 26 Juli 2021 di Yogyakarta adalah 107445 kasus. Jumlah pasien sembuh adalah 71.189, serta jumlah kasus yang meninggal dunia adalah 3.003. Penelitian ini bertujuan utuk mengetahui gambaran tingkat kecemasaan pra operasi di masa pandemic Covid-19 pada tahun 2021. Penelitian ini adalah penelitian kuantitatif dengan pendekatan deskriptif. Populasi dalam penelitian ini adalah masyarakat yang berada di Kota Yogyakarta. Ukuran sampel adalah 96 responden yang dipilih dengan teknik purposive sampling. Data dikumpulkan melalui pengisia kuesioner tentang tingkat kecemasan pra operasi di masa pandemi Covid-19. Data dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa sebagian besar masyarakat Kota Yogyakarta mengalami kecemasan dalam tingkat sedang ketika akan menghadapi operasi pada masa pandemi Covid-19.Kata kunci: kecemasaan; pra operasi; pandemi Covid-19